Study on compatibility of Trichoderma viride with different fungicides - KUMAR, SANJEEV; KUMAR, AMARENDRA; KUMAR, RAKESH; G, RAJESHA (The Indian Journal of Agricultural Sciences, 2022)
Aggressive colonization of T. viride can occurs in diverse environmental condition as a biological control and prevents many soil borne diseases. In this context, laboratory experiment was conducted during 2018-19 at Department of Plant Pathology, Bihar Agricultural University, Sabour, Bhagalpur, Bihar to test the sensitivity of T. viride isolated with selected fungicides to devise the best management practice. In course of investigation, nine fungicides of systemic, non-systemic and their combination were evaluated at lower concentrations compared to recommended dose on sensitivity and sporulation of T. viride with food poisoned techniques. Growth and sporulation of T. viride was totally inhibited by carbendazim, hexoconazole, carbendazim+ mancozeb and iprodione + carbendazim at all the concentrations. Sporulation affected by all the fungicides, but in copper-oxychloride, inhibition of sporulation had minimum, i.e. 19.7, 37.1 and 53.9 at 200, 500 and 1000 μg/ml, respectively. Since, the minimum inhibitory effect on growth and spore production was recorded in copper oxychloride. Thus, the present finding suggest that compatible fungicides copper oxychloride can be used with T. viride in an integrated disease management practices for managing soil borne pathogens.